2020
DOI: 10.1007/s00464-020-07919-4
|View full text |Cite
|
Sign up to set email alerts
|

Transperitoneal vs retroperitoneal minimally invasive partial nephrectomy: comparison of perioperative outcomes and functional follow-up in a large multi-institutional cohort (The RECORD 2 Project)

Abstract: Background Aim of this study was to evaluate and compare perioperative outcomes of transperitoneal (TP) and retroperitoneal (TR) approaches in a multi-institutional cohort of minimally invasive partial nephrectomy (MI-PN). Material and methods All consecutive patients undergone MI-PN for clinical T1 renal tumors at 26 Italian centers (RECORd2 project) between 01/2013 and 12/2016 were evaluated, collecting the pre-, intra-, and postoperative data. The patients were then stratified according to the surgical appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 32 publications
(76 reference statements)
1
19
0
Order By: Relevance
“…Concerning postoperative outcomes, our analysis reported a shorter LOS for patients who underwent R-RAPN (WMD: 0.35 d; p = 0.002). In a recent study, Porpiglia et al [38] compared the retroperitoneal and transperitoneal approaches in 1669 patients who were treated with minimally invasive partial nephrectomy at 26 Italian centers. Overall, the R-RAPN group presented a shorter median LOS (2 vs 3 d; p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning postoperative outcomes, our analysis reported a shorter LOS for patients who underwent R-RAPN (WMD: 0.35 d; p = 0.002). In a recent study, Porpiglia et al [38] compared the retroperitoneal and transperitoneal approaches in 1669 patients who were treated with minimally invasive partial nephrectomy at 26 Italian centers. Overall, the R-RAPN group presented a shorter median LOS (2 vs 3 d; p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…We are able to use this approach in the vast majority of cases, with comparable outcomes to transperitoneal series [5] and only use the transperitoneal approach for anterior hilar tumours (7.4% in the present study). A recently published multi‐institutional matched comparative study of 826 retroperitoneal and transperitoneal RAPNs showed a longer OT for the retroperitoneal approach (115 vs 150 min), but a higher rate of intra‐operative complications (4.3% vs 1.7%) and longer LOS (3 vs 2 days) for the transperitoneal approach, although the results of that study are limited by selection bias [17].…”
Section: Discussionmentioning
confidence: 99%
“…A largest matched pair multi-institutional study in minimally invasive partial nephrectomy, showed that retroperitoneal approach seemed to have a slighter intraoperative complication rate, longer operative times and earlier postoperative recovery when compared with transperitoneal ( 28 ). Although the approach was not exactly the same, it was also confirmed from the side that retroperitoneal approach was better in the overall curative effect of urological surgery.…”
Section: Discussionmentioning
confidence: 99%